Interpreting interreligious relations with Wittgenstein : philosophy, theology, and religious studies - Andrejč, Gorazd (Philosophy of Religion - World Religions, 2019)
This volume argues that Wittgenstein's philosophy of religion and his thought in general continue to be highly relevant for present and future research on interreligious relations. Spanning several (sub)disciplines - from philosophy of religion, philosophy of language, comparative philosophy, comparative theology, to religious studies - the contributions engage with recent developments in interpretation of Wittgenstein and those in the philosophy and theology of interreligious encounter. The book shows that there is an important and under-explored potential for constructive and fruitful engagement between these academic fields. It explores, and attempts to realize, some of this potential by involving both philosophers and theologians, and critically assesses previous applications of Wittgenstein's work in interreligious studies. Contributors are Gorazd Andrejč, Guy Bennett-Hunter, Mikel Burley, Thomas D. Carroll, Paul Cortois, Rhiannon Grant, Randy Ramal, Klaus von Stosch, Varja Štrajn, Nuno Venturinha, Sebastjan Vörös and Daniel H. Weiss.